Engineering trustworthy software systems : 4th International School, SETSS 2018, Chongqing, China, April 7-12, 2018, Tutorial Lectures /: 4th International School, SETSS 2018, Chongqing, China, April 7-12, 2018, Tutorial Lectures. (2019) - Unknown
No abstract available